Novel quantification of formation trend and reaction efficiency of hydroxyl radicals for investigating photocatalytic mechanism of Fe-doped TiO2 during UV and visible light-induced degradation of acid orange 7 - Shen, Jyun-Hong; Chuang, Hung-Yi; Jiang, Zhu-Wu; Liu, Xin-Zhong; Horng, Jao-Jia (Chemosphere (Oxford), 2020)
A detailed mechanistic investigation of the hydroxyl radical (•OH) formation and organic pollutant degradation over transition metal-doped and undoped TiO2 photocatalysts was performed by the quantitative measurement of •OH and the identification of intermediate products under various experimental conditions. The Fe-doped TiO2 as a typical subject was prepared, characterized and used to degrade an azo dye Acid Orange 7 (AO7). It is indicated that the enhanced photocatalytic activity of Fe-doped TiO2 for AO7 degradation was attributed to the increase in surface area, the facilitated charge transfer via Fe-dopant, and a red shift of absorbable wavelength, maintaining a great formation of •OH under visible irradiation. The oxidation of H2O by holes was estimated as the major pathway of •OH formation rather than the reduction of dissolved O2 by electrons, and their formation trends reached to approximately 75% and 25%, respectively. Meanwhile the synergistic effect of Fe-dopant produced nearly 10% of extra •OH by visible light photoactivation. The intermediate products and pathways of AO7 degradation varied greatly with different photocatalysts and conditions of the process, involving several reaction mechanisms such as the azo bond cleaving, naphthalene oxidation, desulfonation, and hydroxylated products generation. Through the quantification of •OH-reacted efficiency we proposed, a stoichiometry of •OH affecting overall reaction mechanisms in the TiO2-assisted photodegradation of AO7 was further established. This study can provide new insights on how to better clarify the variation regularity of organic pollutant degradation from different treatments of the •OH-based advanced oxidation processes. [Display omitted] •Prepared Fe-doped TiO2 exhibited enhanced photocatalytic activity under visible light.•Quantitative mechanism of .•OH formation has reported for Fe-doped TiO2 photocatalysis•Oxidation of H2O by holes dictated the .•OH formation predominance over Fe-doped TiO2•Synergistic effect of Fe-dopant generated extra .•OH via visible light photoactivation•Use of •OH-reacted efficiency shed light on the reaction progress of AO7 degradation